Red mud-based perovskite catalyst as well as preparation method and application thereof

By using red mud as an iron source, combined with the sol-gel method and B-position partial replacement modification technology, a mesoporous structure red mud-based bisperovskite catalyst was prepared, which solved the problems of small specific surface area and poor stability of traditional perovskite catalysts, and achieved efficient antibiotic wastewater degradation effect.

CN119680560APending Publication Date: 2025-03-25UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411846287.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Traditional perovskite catalysts have small specific surface area, poor stability, high cost of metal raw materials, and problems of impurities and grain enlargement during the preparation process, which limits their application performance.

Method used

Red mud is used as the iron source and the mesoporous structure red mud-based bisperovskite catalyst is prepared by sol-gel method combined with B-position partial replacement modification, which improves its specific surface area and pore structure, and enhances microwave energy absorption and catalytic activity.

Benefits of technology

The specific surface area and pore structure of perovskite catalysts are improved, their catalytic activity and thermal stability are enhanced, and they are suitable for the efficient degradation of antibiotic-based organic wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680560A_ABST
    Figure CN119680560A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of microwave catalysis, and particularly relates to a red-mud-based perovskite catalyst and a preparation method and application thereof.The A site of the catalyst is rare earth metal element bismuth, the B site of the catalyst is transition metal element iron, an iron source is red mud, and other transition metal ions are adopted to carry out partial substitution modification on the B site. The preparation method comprises the following steps: dissolving rare earth metal salt, transition metal salt and citric acid in deionized water; adding red mud into the solution obtained in the step S1, and uniformly dispersing; and S2, heating and stirring the mixed phase obtained in the step S2 to a gel state, and drying and calcining the gel to obtain the red mud-based perovskite catalyst. Compared with the prior art, the red mud-based double-perovskite catalyst is prepared by taking industrial waste red mud as an iron source and combining a sol-gel method with B-site partial substitution modification, the red mud-based double-perovskite catalyst shows excellent catalytic degradation performance in the aspect of antibiotic wastewater treatment, and the degradation efficiency of gatifloxacin within 9 min can reach 92% at most.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microwave catalysis, and specifically relates to a red mud-based perovskite catalyst and a preparation method and application thereof. Background Art

[0002] Antibiotics are a typical class of new organic pollutants, which are characterized by a wide variety, complex structure, diverse morphology, and unclear environmental effects. These characteristics make the removal of antibiotics in wastewater the focus and difficulty of water treatment. Advanced oxidation technology (AOPs) is one of the efficient treatment technologies for difficult-to-degrade organic pollutants. Its main feature is to oxidize large-molecule difficult-to-degrade organic matter into low-toxic or non-toxic small-molecule substances under reaction conditions such as high temperature and high pressure, electricity, sound, light irradiation, and catalysts by producing free radicals with strong oxidizing ability. Among them, microwave-assisted persulfate advanced oxidation technology (MW / SR-AOPs) has the advantages of easy operation, fast reaction speed, large amount of reactive species (ROS) generated, and high pollutant degradation efficiency. Microwaves can heat the reaction system quickly and evenly through their unique heating methods (thermal effect and non-thermal effect). Microwave radiation can not only excite persulfate to produce sulfate free radicals (SO4 -· ), and is conducive to exciting the catalyst to generate electron-hole pairs (e - -h + ), the synergistic effect of the three accelerates the electron transfer and the generation of ROS, and promotes the degradation of pollutants. Microwave catalysts play an important role in this system, so the design and preparation of efficient microwave catalysts are of great significance in the degradation of antibiotic organic pollution by MW\SR-AOPs.

[0003] As a new type of metal oxide catalyst, perovskite has strong microwave absorption performance. Due to its low price and high stability, it can be used as an ideal microwave catalyst. Among them, iron-based perovskite usually has excellent persulfate activation ability, rich oxidation states, and good electronic conductivity, and is an ideal MW\SR-AOPs catalyst. However, traditional perovskites have problems such as small specific surface area, poor stability, and low activity, which to a certain extent limit their practical application performance. At the same time, the preparation of traditional perovskites has high metal raw material costs and long reaction time. Under high temperature, the intermediates grow quickly, causing the grains to continue to increase and the activity to decrease, resulting in the prepared perovskite having a low specific surface area and containing impurities. Summary of the invention

[0004] The purpose of the present invention is to provide a red mud-based perovskite catalyst and its preparation method and application in order to solve at least one of the above problems, so as to solve the problems of small specific surface area, poor stability and high cost of metal raw materials of traditional perovskite catalysts in the prior art. The mesoporous red mud-based double perovskite catalyst is prepared by using industrial waste red mud as the iron source through the sol-gel method combined with partial substitution modification at the B position, and it shows excellent catalytic degradation performance in the treatment of antibiotic wastewater.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a red mud-based perovskite catalyst, wherein the catalyst has a rare earth metal element bismuth at position A and a transition metal element iron at position B, and other transition metal ions are used to partially replace and modify the B position, wherein the iron source at position B is red mud.

[0007] Furthermore, the red mud is industrial waste, and using red mud as an iron source not only reduces production costs but also facilitates the recycling of industrial waste.

[0008] Furthermore, the other transition metal ions include Cu 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ and Co 2+ Any of .

[0009] The second technical solution of the present invention is to provide a method for preparing the red mud-based perovskite catalyst as described above, comprising the following steps:

[0010] S1: dissolving rare earth metal salt, transition metal salt and citric acid in deionized water;

[0011] S2: adding red mud to the solution obtained in step S1 and dispersing the mixture evenly to obtain a mixed phase;

[0012] S3: The mixed phase obtained in step S2 is heated and stirred until it is in a gel state, and the gel is dried and calcined to obtain the red mud-based perovskite catalyst.

[0013] Furthermore, the rare earth metal salt in step S1 is Bi(NO3)3·5H2O;

[0014] The transition metal salt includes any one of Cu(NO3)2·6H2O, Mn(NO3)2·4H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Co(NO3)2·6H2O.

[0015] Furthermore, in step S1, the molar ratio of the rare earth metal salt, the transition metal salt and the citric acid is 2:(1-2):(2-4).

[0016] Furthermore, in step S2, the molar ratio of the iron element in the red mud to the rare earth metal salt is (0.5-3.5):2.

[0017] Furthermore, the heating and stirring in step S3 is carried out in a water bath at a temperature of 60 to 80° C., preferably 70° C., for 0.5 to 2 h, preferably 1 h.

[0018] Furthermore, in step S3, the drying temperature is 50-80° C., preferably 60° C., and the drying time is 16-32 hours, preferably 24 hours.

[0019] Furthermore, the calcination in step S3 is carried out in a muffle furnace, the calcination temperature is 500-600° C., the calcination time is 4-8 hours, and the heating rate is 3-5° C. / min.

[0020] After activation, the carbon element in red mud can not only increase the specific surface area of ​​perovskite, optimize the pore structure of perovskite, and improve the defects of traditional perovskite, but also further contribute to the absorption of microwave energy, thereby improving the catalytic activity and accelerating the degradation of pollutants; the composition, crystal structure and morphology of perovskite are regulated by partial substitution of the B position, thereby increasing oxygen vacancies (OVs) and changing the electronic structure and crystal structure, thereby improving the catalytic activity and thermal stability of perovskite.

[0021] The third technical solution of the present invention is to provide an application of the red mud-based perovskite catalyst as described above, wherein the catalyst is used to catalyze the degradation of antibiotic organic wastewater in a microwave-assisted persulfate advanced oxidation process.

[0022] Furthermore, the steps of microwave catalytic degradation of antibiotic wastewater are as follows: adding the catalyst of the present invention and persulfate to the wastewater, reacting under microwave operation to degrade the wastewater; wherein the amount of the catalyst added is 0.5-2.5 g / L, the persulfate concentration is 0.25-2 mM, the microwave power is 300-600 W, and the solution pH is 3-9.

[0023] Furthermore, the persulfate includes any one of peroxymonosulfate (PMS) and peroxydisulfate (PDS).

[0024] Red mud has a loose porous structure and is rich in various metal elements such as iron and aluminum. As one of the raw materials for synthesizing perovskite, it can effectively reduce costs and realize the efficient resource utilization of red mud. In addition, the carbon element in red mud can not only increase the specific surface area of ​​perovskite, optimize the pore structure of perovskite, and improve the defects of traditional perovskite after activation, but also further contribute to the absorption of microwave energy, thereby improving catalytic activity and accelerating the degradation of pollutants. Therefore, this patent uses industrial waste red mud as one of the main metal sources for synthesizing perovskite to prepare red mud-based perovskite. On the other hand, based on the limitations of the catalytic performance of a single iron-based perovskite, the composition, crystal structure and morphology of the perovskite are further regulated by partial substitution of the B position to achieve an increase in oxygen vacancies (OVs), changes in the electronic structure and crystal structure, and thus improve the catalytic activity and thermal stability of the perovskite.

[0025] Therefore, using waste red mud as raw material to prepare red mud-based perovskite can increase the specific surface area of ​​perovskite, increase the pore structure of perovskite, and improve the defects of traditional perovskite. In addition, combined with the method of partial substitution modification at the B position, it can further promote the formation of oxygen vacancies in perovskite oxide to improve its catalytic activity, which is suitable for microwave catalytic degradation reactions of organic matter in a variety of environmental water bodies.

[0026] The present invention is the first attempt to use red mud as raw material, and prepare a mesoporous red mud-based double perovskite catalyst by a sol-gel method combined with partial substitution modification at the B position. The specific surface area of ​​the synthesized perovskite is increased, the pore structure is optimized, and the defects of traditional perovskites are improved. It can not only save costs, but also achieve efficient resource utilization of red mud. At the same time, the introduction of transition metal ions to partially replace the B position of the perovskite is more conducive to the formation of oxygen vacancies in the perovskite lattice structure, increase the concentration of ROS, and further enhance the catalytic activity of the material.

[0027] The present invention limits the addition amount of each component used, the mixing order of each raw material component, the processing temperature and other process parameters, all of which are based on the results of repeated experimental optimization.

[0028] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. The present invention adopts iron-based perovskite as a microwave catalyst for the efficient degradation of antibiotic organic wastewater. The iron-based perovskite can effectively absorb microwave energy and has an excellent activation effect on persulfate. The degradation efficiency of gatifloxacin can reach up to 92% within 9 minutes, which is conducive to accelerating the catalytic reaction. In addition, perovskite is easy to control. By changing the components of perovskite, its electronic structure, energy band structure and surface properties can be adjusted to optimize the catalytic performance.

[0031] 2. The invention uses industrial waste red mud as raw material, which not only saves preparation costs but also realizes efficient resource utilization of red mud. The carbon element in the red mud can increase the specific surface area of ​​perovskite after activation, optimize the pore structure of perovskite, and enhance the absorption of microwave energy, effectively promoting the formation of oxygen vacancies in perovskite, improving the defects of traditional perovskite, and accelerating the degradation of pollutants.

[0032] 3. Through partial substitution modification at the B position, the composition, crystal structure and morphology of perovskite can be regulated, the electron transport performance can be optimized, the redox properties of the surface, the activation ability of oxygen species and the adsorption properties of reactants can be changed, and the intrinsic catalytic reactivity of the perovskite catalyst can be adjusted.

[0033] 4. The preparation steps of the present invention are simple, and the prepared red mud-based perovskite catalyst has excellent performance and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart for preparing the red mud-based perovskite catalyst of the present invention.

[0035] Figure 2 These are SEM images of the perovskite (A) prepared from the traditional medicine in Comparative Example 1 and the red mud-based perovskite (B) in Example 3.

[0036] Figure 3 This is a comparison of the microwave catalytic degradation performance of gatifloxacin by red mud-based perovskites containing different concentrations of iron.

[0037] Figure 4 This is a comparison chart of the microwave catalytic degradation performance of gatifloxacin by the perovskite prepared from the traditional medicine in Comparative Example 1 and the red mud-based perovskite in Example 3. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0039] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.

[0040] The experimental methods without specific conditions in the following implementations are all selected according to conventional methods and conditions, or according to the product instructions. Unless otherwise specified, the experimental instruments used in the present invention are all conventional experimental instruments in the laboratory.

[0041] like Figure 1 As shown, the present invention provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0042] S1: dissolving rare earth metal salt, transition metal salt and citric acid in deionized water;

[0043] S2: adding red mud powder to the solution obtained in step S1, and dispersing the mixture evenly to obtain a mixed phase;

[0044] S3: heating and stirring the mixed phase obtained in step S2 until it becomes a gel;

[0045] S4: drying the gel obtained in step S3;

[0046] S5: calcining the material obtained in step S4 to obtain the red mud-based perovskite catalyst.

[0047] Example 1

[0048] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0049] 2M Bi(NO3)3·5H2O, 1M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 0.5M. Ultrasonic mixing was performed at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 500℃ for 4h at a heating rate of 3℃ / min.

[0050] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 3, 0.5 g / L of the catalyst prepared above and 0.25 mM of the oxidant PDS were added, the mixture was evenly mixed and placed in a microwave catalytic reactor, the microwave power was set to 300 W and the reaction was carried out for 20 min, and the degradation rate of gatifloxacin was calculated according to the absorbance.

[0051] The specific method for calculating the degradation rate of gatifloxacin based on absorbance is as follows:

[0052] The UV-visible spectrum of GAT was measured using an ultraviolet-visible spectrophotometer (UV-vis) with a wavelength range of 200-800 nm, and the characteristic wavelength of GAT was finally determined to be 286 nm. The standard curve is as follows:

[0053] A=0.1303C+0.00231 (R 2 =0.9999) (Formula 1)

[0054] A(Abs) is the absorbance value;

[0055] C (mg / L) is the GAT concentration;

[0056] R 2 is the correlation coefficient of the standard curve.

[0057] The degradation rate of GAT was calculated by formula (2):

[0058]

[0059] C0 (mg / L) is the concentration of GAT before the reaction;

[0060] C t (mg / L) is the concentration of GAT after the reaction.

[0061] Example 2

[0062] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0063] 2M Bi(NO3)3·5H2O, 1.5M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 2.0M. Ultrasonic mixing was carried out at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 550℃ for 6h at a heating rate of 4℃ / min.

[0064] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 5, and 1.5 g / L of the catalyst prepared above and 1 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 450 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0065] Example 3

[0066] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0067] 2M Bi(NO3)3·5H2O, 1M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 2.5M. Ultrasonic mixing was performed at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 500℃ for 4h at a heating rate of 5℃ / min.

[0068] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 0.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 500 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0069] Example 4

[0070] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0071] 2M Bi(NO3)3·5H2O, 2M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 3.5M. Ultrasonic mixing was carried out at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 600℃ for 8h at a heating rate of 5℃ / min to obtain the catalyst.

[0072] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 9, and 2.5 g / L of the above-prepared catalyst and 2 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 600 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0073] Example 5

[0074] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0075] 2M Bi(NO3)3·5H2O, 1M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 1.5M. Ultrasonic mixing was carried out at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 600℃ for 8h at a heating rate of 5℃ / min.

[0076] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 1 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 400 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0077] Example 6

[0078] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0079] 2M Bi(NO3)3·5H2O, 1.5M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 3.0M. Ultrasonic mixing was performed at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 600℃ for 8h at a heating rate of 5℃ / min to obtain the catalyst.

[0080] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 2 g / L of the catalyst prepared above and 1.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 550 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0081] Example 7

[0082] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0083] 2M Bi(NO3)3·5H2O, 1M Ni(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 2.5M. Ultrasonic mixing was performed at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 500℃ for 4h at a heating rate of 5℃ / min.

[0084] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 0.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 500 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0085] Example 8

[0086] This embodiment provides a method for preparing a red mud-based perovskite catalyst, comprising the following steps:

[0087] 2M Bi(NO3)3·5H2O, 1M Co(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 2.5M. Ultrasonic mixing was performed at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst was calcined in a muffle furnace at 500℃ for 4h at a heating rate of 5℃ / min.

[0088] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 0.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 500 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0089] Comparative Example 1

[0090] This comparative example provides a method for preparing a red mud-based perovskite catalyst without B-site doping modification, comprising the following steps:

[0091] 2M Bi(NO3)3·5H2O and 2M citric acid were dissolved in 10mL deionized water, and then red mud was added to make the iron concentration in the solution 2.5M. Ultrasonic mixing was carried out at room temperature for 0.5h, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the red mud-based perovskite catalyst without B-site doping modification was obtained by calcining in a muffle furnace at 500℃ for 4h at a heating rate of 5℃ / min.

[0092] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 0.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 500 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0093] Comparative Example 2

[0094] This comparative example provides a method for preparing a perovskite catalyst using chemical iron salt as an iron source, comprising the following steps:

[0095] 2M Bi(NO3)3·5H2O, 1M Cu(NO3)2·6H2O and 2M citric acid were dissolved in 10mL deionized water, and then the chemical Fe(NO3)3·9H2O was added to make the iron concentration in the solution 2.5M. Ultrasonic mixing was performed for 0.5h at room temperature, and then stirred in a 70℃ water bath for 1h until the gel state was reached, and dried at 60℃ for 24h. Finally, the perovskite catalyst prepared with pure chemical was obtained by calcining in a muffle furnace at 500℃ for 4h at a heating rate of 5℃ / min.

[0096] 50 mL of 20 mg / L gatifloxacin was placed in a three-necked flask, the pH of the solution was adjusted to 7, and 1 g / L of the catalyst prepared above and 0.5 mM of the oxidant PDS were added. After mixing evenly, the mixture was placed in a microwave catalytic reactor, the microwave power was set to 500 W, and the reaction was carried out for 20 minutes. The degradation rate of gatifloxacin was calculated based on the absorbance.

[0097] The perovskite catalysts prepared in Examples 1-9 and Comparative Examples 1-2 were characterized and their performance was measured, wherein the results of Examples 1-4 and Comparative Examples 1-2 are listed below, and the results of Examples 5-9 are similar to those of Example 3, and the results are as follows:

[0098] like Figure 2 As shown, Figure (A) is a perovskite catalyst prepared using chemical iron salt as an iron source in Comparative Example 2, and Figure (B) is a red mud-based perovskite catalyst prepared using red mud as an iron source in Example 3; Figure 2 It can be seen that the surface of the red mud-based perovskite in Example 3 presents a loose sponge-like network structure, with thinner pore walls, smaller pore diameters, and a more developed pore structure. The increase in the roughness of the material surface is beneficial to the improvement of the specific surface area of ​​the catalyst, thereby increasing the number of catalytic active sites.

[0099] like Figure 3 As shown, Figure 3 The catalytic degradation efficiency of gatifloxacin wastewater by different red mud-based perovskites (the concentration of iron in the red mud-based perovskite is in brackets) under microwave induction. As can be seen from the figure, when red mud is added to make the iron content in the red mud-based perovskite 0.5-2.5M, the degradation efficiency of gatifloxacin by red mud-based perovskite increases from 83% to 92% within 9 minutes. When the iron concentration in the red mud-based perovskite is further increased to 3.5M, the degradation rate of gatifloxacin decreases to 85%. When the iron content in the red mud-based perovskite is 2.5M, the synthesized catalyst has the highest activity, and the degradation rate of gatifloxacin reaches 92%.

[0100] like Figure 4 As shown, Figure 4The catalytic degradation efficiency of gatifloxacin wastewater by the perovskite catalyst using chemical iron salt as the iron source in Comparative Example 2 and the red mud-based perovskite catalyst in Example 3 under microwave induction. As can be seen from the figure, when the perovskite is prepared using red mud as the raw material, its degradation efficiency of gatifloxacin is increased from 89% to 92% within 9 minutes. It can be seen that the catalytic performance of the perovskite prepared using red mud as the raw material is also significantly better than that of the perovskite prepared using chemicals.

[0101] The red mud-based perovskite catalysts prepared in Examples 1-4 and Comparative Examples 1-2 were used to perform microwave-induced catalytic degradation experiments on wastewater containing gatifloxacin. The specific process parameters and degradation rates are shown in Table 1.

[0102] Table 1 Specific parameters of Examples 1-7 and Comparative Examples 1-2 and microwave catalytic degradation rates of gatifloxacin

[0103]

[0104] As shown in Examples 1-7 of Table 1, when the catalyst dosage is 1 g / L, the PDS dosage is 0.5 mM, the pH value is 7, the MW power is 500 W, and the iron concentration in the catalyst is 2.5 M, the removal rate of gatifloxacin reaches a maximum of 92%. As shown in Comparative Examples 1-2, the addition of red mud and the doping of Cu(NO3)2·6H2O improve the catalytic activity of the catalyst and the degradation rate of gatifloxacin. Under the same degradation conditions, the performance of red mud-based perovskite (92%) is better than that of perovskite prepared from pharmaceuticals (89%), and the performance of Cu-doped perovskite is better than that of undoped perovskite (79%).

[0105] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A red mud-based perovskite catalyst, characterized in that: The catalyst has a rare earth metal element bismuth at position A and a transition metal element iron at position B, wherein the iron source is red mud, and the B position is partially substituted and modified by transition metal ions, which are non-ferrous metal ions.

2. A red mud-based perovskite catalyst according to claim 1, characterized in that: The transition metal ions include Cu 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ and Co 2+ Any of .

3. A method for preparing a red mud-based perovskite catalyst as claimed in claim 1, characterized in that: The following steps are involved: S1: dissolving rare earth metal salt, transition metal salt and citric acid in deionized water; S2: adding red mud to the solution obtained in step S1 and dispersing the mixture evenly to obtain a mixed phase; S3: The mixed phase obtained in step S2 is heated and stirred until it is in a gel state, and the gel is dried and calcined to obtain the red mud-based perovskite catalyst.

4. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The rare earth metal salt in step S1 is Bi(NO3)3·5H2O; the transition metal salt includes any one of Cu(NO3)2·6H2O, Mn(NO3)2·4H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Co(NO3)2·6H2O.

5. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The molar ratio of the rare earth metal salt, the transition metal salt and the citric acid in step S1 is 2:(1-2):(2-4).

6. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The molar ratio of the iron element in the red mud to the rare earth metal salt in step S2 is (0.5-3.5):

2.

7. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The heating and stirring in step S3 is carried out in a water bath at a temperature of 60 to 80° C. for a time of 0.5 to 2 h.

8. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The drying temperature in step S3 is 50-80° C., and the drying time is 18-32 hours.

9. The method for preparing a red mud-based perovskite catalyst according to claim 3, characterized in that: The calcination in step S3 is carried out in a muffle furnace, the calcination temperature is 500-600° C., the calcination time is 4-8 hours, and the heating rate is 3-5° C. / min.

10. A use of the red mud-based perovskite catalyst as claimed in claim 1, characterized in that: The catalyst is used for catalytic degradation of antibiotic organic wastewater in a microwave-assisted persulfate advanced oxidation process.

Citation Information

Cited By

  • Red mud-based catalyst as well as preparation method and application thereof

    CN120459985A